THE RELATIONSHIP BETWEEN THE LEVEL OF SELF-REFLECTION AND LEVEL OF EMPATHY IN STUDENTS OF MEDICINE FACULTY TANJUNGPURA UNIVERSITY - Rifa Amalia; Ita Armyanti; Ambar Rialita (Universitas Gadjah Mada, 2026)
Background: Providing the best care for patients requires lifelong learning which is an important competency for medical students. Self-reflection is an evaluation of oneself based on experience with the aim of making improvements in the future. Empathy is the ability and skill to understand the feelings of others.Aims: Knowing the relationship between the level of self-reflection and the level of empathy in students of the Medical Study Program, Faculty of Medicine, Tanjungpura University.Methods: This research is an analytic observational method with a Cross-Sectional approach. A total of 168 students were selected using the Stratified Random Sampling technique. Variables were measured using the Self Reflection and Insight Scale (SRIS) questionnaire and the Jefferson Scale of Empathy Student Version (JSE S-Version). Bivariate analysis using Spearman's rho correlation test.Results: The results showed that respondents predominantly had a moderate level of self-reflection (58.3%) and had a high level of empathy (50.6%).Conclusion: There is a statistically significant weak relationship between self-reflection and empathy in students of the Medical Study Program, Faculty of Medicine, Tanjungpura University. Spearman's rho correlation test 0.006 (sig <0.05, r =0.211)